Quick detection of sabbles by using marquis treatment - Sihotang, Herlince; Ginting, Adil; Siburian, Rikson; Simanjuntak, Crystina (Talenta Publisher, 2019)
Methamphetamine or N-methyl-alpha-methyl phenethyl amine is a powerful central nervous system stimulant drug that has an addictive effect when consumed. The number of cases of drug abuse in Indonesia in the last year is most dominated by methamphetamine so that an accurate analysis is needed to detect these compounds. Qualitative rapid detection can be done with marquis reagents which will produce a yellowish green if it is positive for consuming methamphetamine. Student urine samples were extracted with chloroform to separate to form two layers. The top layer filtrate was tested by Marquis reagents. From the test results found no positive Methamphentamine in the urine of class XI IPA students.